Fiscal systems competition: hypotheses and empirical results - Kocia, Agata (Uniwersytet Ekonomiczny we Wrocławiu, 2008)
The aim of this article is to unravel and simplify the vast and complex literature on the subject of tax and fiscal competition. To this end, four of the most famous and useful models are presented - the Tiebout hypothesis, the Leviathan, Zodrow-Mieszkowski and Federal models. Tiebout pioneered this subject of research, concluding that tax competition provides beneficial economic effects. This result was upheld by the originators o f the Leviathan hypothesis, Brennan and Buchanan, but from a viewpoint o f political economy. Some years later, Zodrow and Mieszkowski contradicted the earlier findings by concluding that tax competition may lead to under provision o f public goods/services and/or inefficient allocation of scarce resources. Finally, the federal string of tax competition literature, as exemplified in this article by the work of Feld, Kirchgassner and Schaltegger, returns to it’s beginnings to provide support for the positive effects o f such competition on economic growth. The empirical literature on subject o f competition in taxation is even more diverse. Various authors tried to test the above hypotheses with different results. Some have found that increased tax competition leads to positive results, whereas others found an inverse relation. In those studies it is important to note the sample being tested on as well as variables used, on which the results depend
Argumenta Oeconomica, 2008, No 1 (20), s. 31-44
Keywords: tax competition; tax systems competition; fiscal competition; Tiebout hypothesis; Leviathan hypothesis; Zodrow-Mieszkowski model